Desempenho agronômico e qualidade tecnológica de cultivares de feijão-caupi em função da época de semeadura em Uberaba-MG - Almeida, Fernando da Silva [UNESP] (2014)
Even in expanding to other regions of the country, most of cowpea cultivars were developed for the conditions of the northern and northeastern regions of Brazil. Thus, it is necessary to select cultivars which are more adapted to the environmental conditions of the cerrado, and also the best sowing dates in terms of productivity and technological quality of grain crops. The aim of this study was to evaluate the agronomic performance and technological quality of erect and semi-erect cowpea cultivars depending on sowing under rainfed conditions in Uberaba-MG. The experimental design was randomized blocks, in split plots with four replications. The plots were represented by three sowing dates (12/14/2012, 01/14/2013 and 02/14/2013). The subplots consisted on six cultivars (BRS Guariba Potengi BRS, BRS Cauamé, Novaera BRS, BRS Itaim Tumucumaque and BRS). The experimental subplot consisted on four five feet rows in length, spaced 0.40 meters, and the considered floor area was the two central rows. The agronomic performance and technologic quality of cowpea grain cultivars were influenced by environmental conditions of sowing dates. At sowing in December there was a significant vegetative growth of cowpea cultivars resulting in a lower yield. BRS Tumucumaque was the most productive in sowing done in January. In February, all cultivars had higher grain yields, especially for BRS and BRS Novaera Itaim, with productivity of 3,439 and 3,435 kg ha-1 respectively